Dawru Al-Waqf al-Mu’aqqat fî al-Tamwîl al-Ijtimâ’i fî al-Mashrîfiyah al-Islâmiyah Bî Malayziyâ - Bouhedda Ghalia; Luqman Zakariyah; Yahya Abdullah Al Najjar (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2022)
This research paper aims to study the